Structure and Dynamics of Oxidized Lipoproteins In Vivo: Roles of High-Density Lipoprotein - Itabe, Hiroyuki (Biomedicines, 2021)
Oxidative modification of lipoproteins is implicated in the occurrence and development of atherosclerotic lesions. Earlier studies have elucidated on the mechanisms of foam cell formation and lipid accumulation in these lesions, which is mediated by scavenger receptor-mediated endocytosis of oxidized low-density lipoprotein (oxLDL). Mounting clinical evidence has supported the involvement of oxLDL in cardiovascular diseases. High-density lipoprotein (HDL) is known as anti-atherogenic; however, recent studies have shown circulating oxidized HDL (oxHDL) is related to cardiovascular diseases. A modified structure of oxLDL, which was increased in the plasma of patients with acute myocardial infarction, was characterized. It had two unique features: (1) a fraction of oxLDL accompanied oxHDL, and (2) apoA1 was heavily modified, while modification of apoB, and the accumulation of oxidized phosphatidylcholine (oxPC) and lysophosphatidylcholine (lysoPC) was less pronounced. When LDL and HDL were present at the same time, oxidized lipoproteins actively interacted with each other, and oxPC and lysoPC were transferred to another lipoprotein particle and enzymatically metabolized rapidly. This brief review provides a novel view on the dynamics of oxLDL and oxHDL in circulation.